2010
DOI: 10.1038/ismej.2010.76
|View full text |Cite
|
Sign up to set email alerts
|

[FeFe]-hydrogenase in Yellowstone National Park: evidence for dispersal limitation and phylogenetic niche conservatism

Abstract: Hydrogen (H 2 ) has an important role in the anaerobic degradation of organic carbon and is the basis for many syntrophic interactions that commonly occur in microbial communities. Little is known, however, with regard to the biotic and/or abiotic factors that control the distribution and phylogenetic diversity of organisms which produce H 2 in microbial communities. In this study, we examined the [FeFe]-hydrogenase gene (hydA) as a proxy for fermentative bacterial H 2 production along physical and chemical gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
94
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(103 citation statements)
references
References 54 publications
8
94
1
Order By: Relevance
“…Hydrogenase sequences taken from T. primitia ZAS-2 and T. primitia ZAS-9 are labeled as ZAS-2 (HndA1) and ZAS-9 (HndA), respectively. drogenase sequences from unique ecosystems, as evidenced by sequence similarity and uniqueness, have been reported by Ballor and Leadbetter and by Boyd et al (2,5,6).…”
Section: High [Fefe] Hydrogenase Sequence Diversity In Higher Termitesmentioning
confidence: 92%
See 1 more Smart Citation
“…Hydrogenase sequences taken from T. primitia ZAS-2 and T. primitia ZAS-9 are labeled as ZAS-2 (HndA1) and ZAS-9 (HndA), respectively. drogenase sequences from unique ecosystems, as evidenced by sequence similarity and uniqueness, have been reported by Ballor and Leadbetter and by Boyd et al (2,5,6).…”
Section: High [Fefe] Hydrogenase Sequence Diversity In Higher Termitesmentioning
confidence: 92%
“…Functional variation is known to be linked to increased ecosystem function (45). In their study of hydrogenase sequence diversity and phylogeny, Boyd et al propose that an increase in phylogenetic diversity that they observed in slightly acidic geothermal springs may result in a more resilient community able to "better respond to change in both physical and chemical conditions in these environments due to seasonal hydrological and chemical changes" (5).…”
Section: High [Fefe] Hydrogenase Sequence Diversity In Higher Termitesmentioning
confidence: 99%
“…Microcosm assays were conducted to determine the affinity constant (K m ; the concentration at which the formate conversion velocity reaches one-half of its maximum rate) for chemosynthetic microbial communities in the same 5 10.0 M. Microcosms were prepared, incubated, and analyzed for formate conversion activity as described below. To determine formate conversion rates, the rate at which CO 2 was produced from formate oxidation (the methods are described below) was combined with the rate of C assimilation from formate.…”
Section: Methodsmentioning
confidence: 99%
“…ife in environments with temperatures that exceed the upper limit of photosynthesis (ϳ73°C) is supported by chemical energy (1)(2)(3)(4)(5). In the case of high-temperature (Ͼ73°C) terrestrial hot spring environments, the prevalence of members of the bacterial phylum Aquificales has been interpreted to reflect the importance of lithoautotrophic metabolism in supporting communities inhabiting these systems (6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…So far, the high diversity of [FeFe]-hydrogenases has been studied both in natural environments [25][26][27] and several pilot scale plants for H2 production [28][29][30].…”
mentioning
confidence: 99%